2012
DOI: 10.1016/j.jfineco.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Difference in interim performance and risk taking with short-sale constraints

Abstract: Absent much theory, empirical works often rely on the following informal reasoning when looking for evidence of a mutual fund tournament: If there is a tournament, interim winners have incentives to decrease their portfolio volatility as they attempt to protect their lead, while interim losers are expected to increase their volatility so as to catch up with winners. We consider a rational model of a mutual fund tournament in the presence of short-sale constraints and find the opposite-interim winners choose mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Subsequently, using US fund data from 1976 to 2001, Goriaev et al (2005) confirmed the conclusion of Busse (2001). Furthermore, Basak and Makarov (2012) considered a rational model of a mutual fund tournament with constraints on shortselling and found that interim winners select more volatile portfolios than interim losers. They also demonstrated that tournament incentives influence interim performance for otherwise identical managers, and that mid-year trading volume is inversely related to mid-year stock return.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Subsequently, using US fund data from 1976 to 2001, Goriaev et al (2005) confirmed the conclusion of Busse (2001). Furthermore, Basak and Makarov (2012) considered a rational model of a mutual fund tournament with constraints on shortselling and found that interim winners select more volatile portfolios than interim losers. They also demonstrated that tournament incentives influence interim performance for otherwise identical managers, and that mid-year trading volume is inversely related to mid-year stock return.…”
Section: Introductionmentioning
confidence: 65%
“…For the eight models, previous studies obtain the following inferences regarding the regression coefficients: a 2 , β 1 , β 2 and δ 1 . That is, a 2 > 0 in Chen and Pennacchi (2009); β 1 < 0 and δ 1 > 0 in Brown et al (1996), Chevalier and Ellison (1999), Chen and Pennacchi (2009), Pennacchi and Rastad (2011) and Basak and Makarov (2012); β 1 ¼ 0 and δ 1 ¼ 0 in Renneboog et al (2011) and Cullen et al (2012); β 2 < 0 in Kempf and Ruenzi (2008); and β 2 ¼ 0 in Chen and Pennacchi (2009).…”
Section: Downloaded By [Stockholm University Library] At 19:58 19 Augmentioning
confidence: 99%
“…Contrary to the majority of the positive theoretical literature on fund tournaments (Basak and Makarov, 2012), the above model does not assume a convex flow-performance relation. Although there is some evidence that the flow-performance relation for MMFs is convex (Christoffersen and Musto, 2002), that risk-taking channel is shut off to focus on the incentives generated by the tournament nature of fund competition alone.…”
Section: Discussion Of Model's Assumptionsmentioning
confidence: 94%
“…Under a technical point of view, most theoretical papers on fund tournaments consider tournaments with only two players (winner and loser). Basak and Makarov (2012) solve a tournament with a continuum of funds assuming that a fund's payoff only depends on its performance relative to the population average. The methodological contribution of this paper is to develop a technique to solve tournaments with a continuum of players without resorting to such approximations.…”
Section: Related Literaturementioning
confidence: 99%
“…Tournaments take place not only in a given fund segment, but also within families of funds that belong to the same controlling group but offer On the theoretical side, a vast literature has modelled mutual fund tournaments and challenged the narrow-sense risk-shifting hypothesis, that losers gamble and winners index (Acker and Duck, 2006;Basak and Makarov, 2010;Basak, Pavlova and Shapiro, 2007;Chen and Pennacchi, 2009;Goriaev, Palomino and Prat, 2001;Taylor, 2003). The degree of risk tolerance affects the risk-ranking relationship and, under risk neutrality, may even cause winners to gamble (Basak and Makarov, 2010).…”
Section: Ecb Working Paper Series No 1377mentioning
confidence: 99%